Homework in Functional Analytic Psychotherapy (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Therapeutic effects of homework in Functional Analytic Psychotherapy (FAP) are still poorly documented. The objective of the study was to assess relations between homework and its report. The method consisted in recording and coding thirteen sessions of a FAP treatment. A 39-year-old man, who complained about interpersonal difficulties, was the participant. An A/B/A/B design was conducted, and interventions without and with homework were alternated. Data were analyzed by verifying relations among homework proposal, its execution, and subsequent clinical improvement. Additionally, the correspondence between homework proposal and reports about its execution were compared. Results indicated that reports about homework were consistent to its proposal. Attention to homework graduating and advantages of using smartphones to monitor homework were discussed.
Keywords: homework; functional analytic psychotherapy; self-record; client-therapist interaction